Epidemiology of cervical cancer development- a hospital based study - Chandana Ray Das; Sujoy Bose; Manab Deka; Diptika Tiwari; Purabi Deka Bose; Gokul Ch Das (International Journal of Medical Research and Review, 2015)
Introduction: The present study is an attempt to detect Human papilloma virus infection and immunomodulation status in the development of carcinoma cervix.Methods: Cervical cancer cases were enrolled in between Jan’ 2010 to Dec’ 2012. Cervical tissue biopsies from the both the cancerous region as well as the non cancerous control area of the cervix, and whole blood (3ml) were collected from all the study subjects. The tissue samples were collected either in PBS or RNA later solution in vials and stored in -80°C or liquid nitrogen till further use. Whole blood (2ml) was also collected from age matched voluntary female community controls (n=50), the plasma was separated, and stored at -20°C for cytokine analysis. Extracted DNA was then checked for presence of HPV DNA by PCR amplification method using MY09/11 primer. Th1 (IL-12) and Th2 (IL-10) were analysed both at protein as well as cervical tissue level.Results: The study showed 83.33% cases found to be HPV positive in cancerous area as well as in non cancerous area. There were other significant risk factor association of cervical cancer with early marriage in 70.36% and high parity 87% of cases. There is alteration of Th1 and Th2 ratio indicating immunomodulation plays an important role in the development of cervical cancer.Conclusion: The human papilloma virus infections are the major contributing factor as well as immunomodulation plays a major role in the development of cervical cancer in our region.